Myocardial Infarction as an Early Presentation in Thrombotic Thrombocytopenic Purpura: A Rare Case Series - Sumit Dahal MBBS; Dipesh K. C. Ghimire MBBS; Saroj Sapkota MBBS; Suyash Dahal MBBS; Paritosh Kafle MBBS; Manjul Bhandari MBBS (SAGE Publishing, 2018)
Renal and neurological involvements are frequently seen in thrombotic thrombocytopenic purpura (TTP). Cardiac involvement, however, has been rarely reported. In this article, we present 2 cases of myocardial infarction in patients with TTP. In the first case, a young man presented with non-ST-segment elevation myocardial infarction that resolved promptly with plasmapheresis. The second patient developed ST-segment elevation myocardial infarction early in the course of the disease and died before plasmapheresis could be initiated. Hence, a high degree of suspicion with prompt diagnosis and treatment is needed to prevent mortality associated with cardiac involvement in TTP.